Predicting the outcome of initial non-surgical endodontic procedures by periapical status and quality of root canal filling: a cohort study (2020)
To assess the previous periapical status and the quality of root canal filling as predictors of the outcome in initial non-surgical endodontic procedures. A retrospective cohort study was designed in which the presence of a previous periapical lesion was determined radiographically. The quality of the root filling was evaluated in terms of homogeneity, taper, and apical extension. The response variable was dichotomized to success and failure. Bivariate analyzes and a mixed generalized linear model interpreted the association between the explanatory variables and the outcome of the initial non-surgical endodontic procedures. A total of 349 roots were evaluated, and a failure rate of 13.18% was established. Poor filling quality was determined in 8.3% of the roots. As a main result, the presence of a preoperative periapical lesion did not determine a significant risk to the failure of the initial treatment. Unlike, a poor quality of the obturation determined association with an unfavorable outcome like this: (1) homogeneity (OR 2.32; p = 0.0181); (2) taper (OR 5.8; p = 0.0); and, (3) extension (OR 3.41; p = 0.0). Therefore, a significant association between inadequate quality of the root filling and failure of the primary non-surgical endodontic procedures was found. Short length of filling was highly associated with failure. The presence of previous periapical lesion was not found to be a significant predictor for treatment outcomes. © 2020, The Society of The Nippon Dental University.